2016
DOI: 10.5120/ijca2016912251
|View full text |Cite
|
Sign up to set email alerts
|

DDOS Protection by Dividing and Limiting

Abstract: DDOS attacks have increased lately to an extent where large companies have lost millions. They pose a large threat to internet security. This paper explains DOS and DDOS attacks and their types as well as two computer softwares -LOIC and DDOSIM -to launch DDOS attacks and the history of the well-known botnets and DDOS attacks. A solution for DDOS protection at application layer is also proposed. It explores the combination of various tools and techniques like ingress filtering, IP address blacklist checker and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…If it is an IP based device, then the IP address of the device is changed in the routing table. For a BLE or a Zigbee device, an alert is shown that the corresponding device is under a DoS attack (Algorithm 3: Line [23][24][25][26][27][28][29]. Similarly, if the outgoing packets for an IP device exceed its threshold, then the device is removed from the IoT network.…”
Section: Owl Defensementioning
confidence: 99%
See 2 more Smart Citations
“…If it is an IP based device, then the IP address of the device is changed in the routing table. For a BLE or a Zigbee device, an alert is shown that the corresponding device is under a DoS attack (Algorithm 3: Line [23][24][25][26][27][28][29]. Similarly, if the outgoing packets for an IP device exceed its threshold, then the device is removed from the IoT network.…”
Section: Owl Defensementioning
confidence: 99%
“…For conducting DoS attacks we have used our OWL framework and also used state of the art tools (LOIC [12] and hping3 [13]) for the fair comparison. The reason for choosing LOIC and hping3 is due to their ability to perform various types of DoS attacks namely TCP, UDP, and HTTP in a sophisticated manner with a high magnitude of impact [25]. However, both the tools are chosen have their drawbacks when compared to our OWL framework for attack purpose regarding performance, attack methods and surface, holistic inclusion of IP, Bluetooth and Zigbee IoT devices.…”
Section: Denial Of Servicementioning
confidence: 99%
See 1 more Smart Citation